Cecilia - Chang, K-Ming (Coffee House Press, 2024)
"A surreal novella about the intensity and eroticism of girlhood friendships, the ecstasy of desire and disgust, and matriarchal mythmaking. Seven, who works as a cleaner at a chiropractor's office, reencounters Cecilia, a woman who has obsessed her since their school days. Their chance meeting spurs a series of intensely vivid and corporeal memories, and also leads to a bus ride during which each claims dubiously not to be following the other. In the defamiliarization that follows, the narrator begins to experience queerness as an alienation from normative time. Smart, subversive, and gripping, Cecilia is a novella about queerness, obsessive love, inextricable histories of desire and violence, diaspora, and bodily transformation."--